METHOD OF BATIK PAINTING CREATION - Hamzah; Rian, Rica; Yandri, Yandri (ISI Press Institut Seni Indonesia Surakarta, 2025)
The research aims to explore how batik painting works and how to apply the method in batik painting. This research uses an artistic research type, with stages, namely exploration, design, and visualization. Batik painting works are almost the same as painted batik, but there are fundamental differences between the two, even though they both use batik materials: painted batik works emphasize canting in the process, while batik painting predominantly uses brushes, and only canting is used for use. Two works were presented: The first is entitled “Menua Asa 1”, measuring 170 x 130 cm, which uses batik painting techniques. The second work, entitled “Menua Asa 2”, measuring 170 x 130 cm, also uses batik painting techniques